Development of an E-Commerce System to Enhance OfficeSupply Sales Efficiency: A Case Study of XYZ - ม้าสุวรรณ ธีรนันท์; พรมดี ภคมน; เหรียญทอง เวธน์วศิน; ส่วยสิน พัชรินทร์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
XYZ store operates a traditional office supply business, which experiences delays in order management, lacks the ability for customers to self-check and compare products, and suffers from inefficient data management. Therefore, this research aimed to (1) develop an e-commerce system to enhance office supply sales efficiency, a case study of XYZ store, supporting product display, membership registration, ordering, payment, and data management; (2) evaluate the system quality by experts; and (3) assess user satisfaction. This research applied the System Development Life Cycle (SDLC) framework for system development. The sample consisted of 3 experts and 30 actual users. Data were analyzed using mean and standard deviation. The results indicated that the system functioned completely according to the specified requirements, reducing the store’s operational steps compared to the traditional business model. The overall system quality evaluation by experts showed a mean score of 3.95 (S.D. = 1.13) at a high level, while the user satisfaction evaluation showed an overall mean score of 4.39 (S.D. = 0.79), also at a high level. It can be concluded that the developed e-commerce system is efficient, capable of solving operational delays, expanding customer reach, and appropriate for practical implementation to support business operations.